Modeling and simulation of metallic, particle-damped spheres for lightweight materials - Steinle, Tobias
Lightweight materials play an ever growing role in today's world. Saving on the mass of a machine will usually translate into a lower energy consumption. However, lightweight applications are prone to develop performance problems due to vibration induced by the operation of the machine. The Fraunhofer Institute for Manufacturing Technology and Advanced Materials in Dresden conducts research into the damping properties of composite materials. They are experimenting with hollow, particle filled spheres embedded in the lightweight material. Such a system is the technical motivation of this thesis. Ultimately, a numerical experiment to derive the coefficient of restitution is required. The simulation developed in this thesis is based on a discrete element method to track the individual particle and sphere trajectories. Based on a potential based approach for the particle interactions deployed in molecular dynamics, the behavior of the particles can be controlled effectively. The simulated volume is using reflecting boundaries and encloses the hollow sphere. In this work, a highly flexible memory structure was used with a linked cell approach to cope with the highly flexible mass of particles. This allows for a linear complexity of the method in regard to the particle number by reducing the computational overhead of the interaction computation. Multiple numerical experiments show the great effect the particles have on the damping behavior of the system.

Monitoring in Franchise-Netzwerken: Eine ökonomische Analyse - Breuer, Robin

Informationsasymmetrien auf dem Spendenmarkt und Möglichkeiten ihrer Reduktion: Eine Prinzipal-Agenten-Perspektive von Online Spenden - Amedick, Michaela

Pairwise versus Pointwise Ranking: A Case Study - Melnikov, Vitalik; Hüllermeier, Eyke; Kaimann, Daniel; Frick, Bernd; Gupta, Pritha (Schedae Informaticae)

Multiobjective Optimal Control Methods for the Development of an Intelligent Cruise Control - Dellnitz, Michael; Eckstein, Julian; Flaßkamp, Kathrin; Friedel, Patrick; Horenkamp, Christian; Köhler, Ulrich; Ober-Blöbaum, Sina; Peitz, Sebastian; Tiemeyer, Sebastian (Progress in Industrial Mathematics at ECMI)

Second harmonic generation spectroscopy on hybrid plasmonic/dielectric nanoantennas - Linnenbank, Heiko; Grynko, Yevgen; Förstner, Jens; Linden, Stefan (Light: Science & Applications)
Keywords: tet_topic_opticalantenna; tet_topic_shg

Oblique incidence of semi-guided waves on step-like folds in planar dielectric slabs: Lossless vertical interconnects in 3D integrated photonic circuits - Hildebrandt, Andre; Alhaddad, Samer; Hammer, Manfred; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XX)
Keywords: tet_topic_waveguide

Bildungsarbeit in Wirtschaft und Betrieb - Harteis, Christian; Heid, Helmut (Handbuch Bildungsforschung)

A News Editorial Corpus for Mining Argumentation Strategies - Al Khatib, Khalid; Wachsmuth, Henning; Kiesel, Johannes; Hagen, Matthias; Stein, Benno (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: Technical Papers)

Silicon oxynitride microdisk resonators for integrated waveguide coupling - Hett, Thomas; Frers, Torsten; Widhalm, Alex; Berth, Gerhard; Hilleringmann, Ulrich; Zrenner, Artur (Smart Systems Integration 2016 - International Conference and Exhibition on Integration Issues of Miniaturized Systems, SSI 2016)

Cross-Domain Mining of Argumentative Text through Distant Supervision - Al-Khatib, Khalid; Wachsmuth, Henning; Hagen, Matthias; Köhler, Jonas; Stein, Benno (Proceedings of the 2016 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies)

A News Editorial Corpus for Mining Argumentation Strategies - Al Khatib, Khalid; Wachsmuth, Henning; Kiesel, Johannes; Hagen, Matthias; Stein, Benno (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: Technical Papers)

Using Argument Mining to Assess the Argumentation Quality of Essays - Wachsmuth, Henning; Al Khatib, Khalid; Stein, Benno (Proceedings of COLING 2016, the 26th International Conference on Computational Linguistics: Technical Papers)

Light scattering by ice crystals of cirrus clouds: From exact numerical methods to physical-optics approximation - Konoshonkin, Alexander; Borovoi, Anatoli; Kustova, Natalia; Okamoto, Hajime; Ishimoto, Hiroshi; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The problem of light scattering by ice crystals of cirrus clouds is considered in the case of a hexagonal ice plate with different distributions over crystal orientations. The physical-optics approximation based on (E, M)-diffraction theory is compared with two exact numerical methods: the finite difference time domain (FDTD) and the discontinuous Galerkin time domain (DGTD) in order to estimate its accuracy and limits of applicability. It is shown that the accuracy of the physical-optics approximation is estimated as 95% for the averaged backscattering Mueller matrix for particles with size parameter more than 120. Furthermore, the simple expression that allows one to estimate the minimal number of particle orientations required for appropriate spatial averaging has been derived.
Keywords: tet_topic_scattering

Comparison between the physical-optics approximation and exact methods solving the problem of light scattering by ice crystals of cirrus clouds - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Okamoto, H.; Sato, K.; Ishimoto, H.; Grynko, Yevgen; Förstner, Jens (22nd International Symposium on Atmospheric and Ocean Optics: Atmospheric Physics)
In the problem of light scattering by ice crystals of cirrus clouds, two exact methods (FDTD – finite difference time domain and DGTD – discontinuous Galerkin time domain) and the physical-optics approximation are used for numerical calculations of the Mueller matrix in the case of ice hexagonal plates and columns. It is shown that for the crystals larger than 10 μm at the wavelength of 0.532 μm the exact methods and physical-optics approximation closely agreed within three diffraction fringes about the centers of the diffraction patterns. As a result, in the case of random orientation of these crystals, the physical-optics approximation provides accuracy 95% for the averaged Mueller matrix.
Keywords: tet_topic_scattering

Phase sensitive properties and coherent manipulation of a photonic crystal microcavity - Quiring, Wadim; Jonas, Björn; Förstner, Jens; Rai, Ashish K.; Reuter, Dirk; Wieck, Andreas D.; Zrenner, Artur (Optics Express)
We present phase sensitive cavity field measurements on photonic crystal microcavities. The experiments have been performed as autocorrelation measurements with ps double pulse laser excitation for resonant and detuned conditions. Measured E-field autocorrelation functions reveal a very strong detuning dependence of the phase shift between laser and cavity field and of the autocorrelation amplitude of the cavity field. The fully resolved phase information allows for a precise frequency discrimination and hence for a precise measurement of the detuning between laser and cavity. The behavior of the autocorrelation amplitude and phase and their detuning dependence can be fully described by an analytic model. Furthermore, coherent control of the cavity field is demonstrated by tailored laser excitation with phase and amplitude controlled pulses. The experimental proof and verification of the above described phenomena became possible by an electric detection scheme, which employs planar photonic crystal microcavity photo diodes with metallic Schottky contacts in the defect region of the resonator. The applied photo current detection was shown to work also efficiently at room temperature, which make electrically contacted microcavities attractive for real world applications.
Keywords: tet_topic_phc

Light scattering by irregular particles much larger than the wavelength with wavelength-scale surface roughness - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optics Letters)
We simulate light scattering by random irregular particles that have dimensions much larger than the wavelength of incident light at the size parameter of 𝑋=200 using the discontinuous Galerkin time domain method. A comparison of the DGTD solution for smoothly faceted particles with that obtained with a geometric optics model shows good agreement for the scattering angle curves of intensity and polarization. If a wavelength-scale surface roughness is introduced, diffuse scattering at rough interface results in smooth and featureless curves for all scattering matrix elements which is consistent with the laboratory measurements of real samples.
Keywords: tet_topic_scattering

Light scattering by ice crystals of cirrus clouds: comparison of the physical optics methods - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The physical optics approximations are derived from the Maxwell equations. The scattered field equations by Kirchhoff, Stratton-Chu, Kottler and Franz are compared and discussed. It is shown that in the case of faceted particles, these equations reduce to a sum of the diffraction integrals, where every diffraction integral is associated with one plane–parallel optical beam leaving a particle facet. In the far zone, these diffraction integrals correspond to the Fraunhofer diffraction patterns. The paper discusses the E-, M- and (E, M)-diffraction theories as applied to ice crystals of cirrus clouds. The comparison to the exact solution obtained by the discontinuous Galerkin time domain method shows that the Kirchhoff diffraction theory is preferable.
Keywords: tet_topic_scattering

Pipelines Für Effiziente und Robuste Ad-hoc Textanalyse - Wachsmuth, Henning (Ausgezeichnete Informatikdissertationen 2015)

Discrete plasmonic solitons in graphene-coated nanowire arrays - Kou, Yao; Förstner, Jens (Optics Express)
e study the discrete soliton formation in one- and two- dimensional arrays of nanowires coated with graphene monolayers. Highly confined solitons, including the fundamental and the higher-order modes, are found to be supported by the proposed structure with a low level of power flow. Numerical analysis reveals that, by tuning the input intensity and Fermi energy, the beam diffraction, soliton dimension and propagation loss can be fully controlled in a broad range, indicating potential values of the graphene-based solitons in nonlinear/active nanophotonic systems.
Keywords: tet_topic_plasmonics; tet_topic_polariton

The role of electromagnetic interactions in second harmonic generation from plasmonic metamaterials - Alberti, Julian; Linnenbank, Heiko; Linden, Stefan; Grynko, Yevgen; Förstner, Jens (Applied Physics B)
We report on second harmonic generation spectroscopy on a series of rectangular arrays of split-ring resonators. Within the sample series, the lattice constants are varied, but the area of the unit cell is kept ﬁxed. The SHG signal intensity of the different arrays upon resonant excitation of the fundamental plasmonic mode strongly depends on the respective arrangement of the split-ring resonators. This ﬁnding can be explained by variations of the electromagnetic interactions between the split-ring resonators in the different arrays. The experimental results are in agreement with numerical calculations based on the discontinuous Galerkin time-domain method. (PDF) The role of electromagnetic interactions.... Available from: https://www.researchgate.net/publication/297612326_The_role_of_electromagnetic_interactions_in_second_harmonic_generation_from_plasmonic_metamaterials [accessed Aug 13 2018].
Keywords: tet_topic_shg; tet_topic_meta

Searchable Encryption - Weis, Eduard

Vertiefende Analysen zu ICILS 2013 – Befunde und mögliche Entwicklungsperspektiven - Eickelmann, Birgit; Gerick, Julia; Drossel, Kerstin; Bos, Wilfried (ICILS 2013 - Vertiefende Analysen zu computer- und informationsbezogenen Kompetenzen von Jugendlichen)

Singular Curve Point Decompression Attack - Blömer, Johannes; Günther, Peter (2015 Workshop on Fault Diagnosis and Tolerance in Cryptography (FDTC))

Implementing Cryptographic Pairings on Accumulator Based Smart Card Architectures - Günther, Peter; Krummel, Volker (Mathematical Aspects of Computer and Information Sciences)

Theoretical Analysis of the k-Means Algorithm – A Survey - Blömer, Johannes; Lammersen, Christiane; Schmidt, Melanie; Sohler, Christian (Algorithm Engineering)

Hard-Clustering with Gaussian Mixture Models - Blömer, Johannes; Brauer, Sascha; Bujna, Kathrin

Adaptive Seeding for Gaussian Mixture Models - Blömer, Johannes; Bujna, Kathrin (Advances in Knowledge Discovery and Data Mining)

Effizienz und Sicherheit paarungsbasierter Kryptographie - Blömer, Johannes; Günther, Peter

On Non-Cooperative Foundation and Implementation of the Nash Solution in Subgame Perfect Equilibrium via Rubinstein's Game - Duman, Papatya; Trockel, Walter (Journal of Mechanism and Institution Design)

Tightly secure signatures and public-key encryption - Hofheinz, Dennis; Jager, Tibor (Des. Codes Cryptography)

Selective opening security of practical public-key encryption schemes - Heuer, Felix; Jager, Tibor; Schäge, Sven; Kiltz, Eike (IET Information Security)

Black-Box Accumulation: Collecting Incentives in a Privacy-Preserving Way - Jager, Tibor; Rupp, Andy (PoPETs)

How to Generate and Use Universal Samplers - Hofheinz, Dennis; Jager, Tibor; Khurana, Dakshita; Sahai, Amit; Waters, Brent; Zhandry, Mark (Advances in Cryptology - ASIACRYPT 2016 - 22nd International Conference on the Theory and Application of Cryptology and Information Security, Hanoi, Vietnam, December 4-8, 2016, Proceedings, Part II)

Breaking PPTP VPNs via RADIUS Encryption - Horst, Matthias; Grothe, Martin; Jager, Tibor; Schwenk, Jörg (Cryptology and Network Security - 15th International Conference, CANS 2016, Milan, Italy, November 14-16, 2016, Proceedings)

On the Impossibility of Tight Cryptographic Reductions - Bader, Christoph; Jager, Tibor; Li, Yong; Schäge, Sven (Advances in Cryptology - EUROCRYPT 2016 - 35th Annual International Conference on the Theory and Applications of Cryptographic Techniques, Vienna, Austria, May 8-12, 2016, Proceedings, Part II)

Public-Key Encryption with Simulation-Based Selective-Opening Security and Compact Ciphertexts - Hofheinz, Dennis; Jager, Tibor; Rupp, Andy (Theory of Cryptography - 14th International Conference, TCC 2016-B, Beijing, China, October 31 - November 3, 2016, Proceedings, Part II)

Verifiable Random Functions from Standard Assumptions - Hofheinz, Dennis; Jager, Tibor (Theory of Cryptography - 13th International Conference, TCC 2016-A, Tel Aviv, Israel, January 10-13, 2016, Proceedings, Part I)

Verification of AUTOSAR Software Architectures with Timed Automata - Beringer, Steffen; Wehrheim, Heike (Critical Systems: Formal Methods and Automated Verification - Joint 21st International Workshop on Formal Methods for Industrial Critical Systems and 16th International Workshop on Automated Verification of Critical Systems, FMICS-AVoCS 2016, Pisa, Italy, September 26-28, 2016, Proceedings)

Verification of Concurrent Programs on Weak Memory Models - Travkin, Oleg; Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2016 - 13th International Colloquium, Taipei, Taiwan, ROC, October 24-31, 2016, Proceedings)

Towards a Thread-Local Proof Technique for Starvation Freedom - Schellhorn, Gerhard; Travkin, Oleg; Wehrheim, Heike (Integrated Formal Methods - 12th International Conference, IFM 2016, Reykjavik, Iceland, June 1-5, 2016, Proceedings)

Proving Opacity of a Pessimistic STM - Doherty, Simon; Dongol, Brijesh; Derrick, John; Schellhorn, Gerhard; Wehrheim, Heike (20th International Conference on Principles of Distributed Systems, OPODIS 2016, December 13-16, 2016, Madrid, Spain)

Deriving approximation tolerance constraints from verification runs - Isenberg, Tobias; Jakobs, Marie{-}Christine; Pauck, Felix; Wehrheim, Heike (CoRR)

Can the Crowd Substitute Experts in Evaluation of Creative Ideas? An Experimental Study Using Business Models - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 22nd Americas' Conference on Information Systems (AMCIS))

Can the Crowd Substitute Experts in Evaluation of Creative Jobs? The Case of Business Models - Görzen, Thomas; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Read this Paper! A Field Experiment on the Role of a Call-To-Action in Paid Search - Schlangenotto, Darius; Kundisch, Dennis (Proceedings of the 24th European Conference on Information Systems (ECIS))

Fitness and fatness in relation with attention capacity in European adolescents: The HELENA study - Cadenas-Sanchez, Cristina; Vanhelst, Jeremy; Ruiz, Jonatan R.; Castillo-Gualda, Ruth; Libuda, Lars; Labayen, Idoia; De Miguel-Etayo, Pilar; Marcos, Ascensión; Molnár, Eszter; Catena, Andrés; Moreno, Luis A.; Sjöström, Michael; et al. (Journal of Science and Medicine in Sport)

Sedentary Behavior Is Independently Related to Fat Mass among Children and Adolescents in South China - Xue, Hongmei; Tian, Guo; Duan, Ruonan; Quan, Liming; Zhao, Li; Yang, Min; Libuda, Lars; Muckelbauer, Rebecca; Cheng, Guo (Nutrients)

Lunch at school and children’s cognitive functioning in the early afternoon: results from the Cognition Intervention Study Dortmund Continued (CoCo) - Schröder, Maike; Müller, Katrin; Falkenstein, Michael; Stehle, Peter; Kersting, Mathilde; Libuda, Lars (British Journal of Nutrition)
Abstract Studies about effects of school lunch on children’s cognition are rare; two previous studies (CogniDo, CogniDo PLUS) generally found no negative effects of lunch on children’s cognitive performance at the end of lunch break (i.e. 45 min after finishing lunch), but suggested potential beneficial effects for single parameters. Therefore, the present study investigated the hypothesis of potential positive effects of school lunch on cognitive performance at early afternoon (90 min after finishing lunch). A randomised, cross-over intervention trial was conducted at a comprehensive school with fifth and sixth grade students. Participants were randomised into two groups: On day 1, group 1 did not eat lunch, whereas group 2 received lunch ad libitum . On day 2 (1 week later), group 2 did not eat lunch and group 1 received lunch ad libitum . The cognitive parameters task switching, working memory updating and alertness were tested using a computerised test battery 90 min after finishing the meal. Of the 204 recruited children, fifty were excluded because of deviations from the study protocol or absence on one of the 2 test days, which resulted in 154 participants. Data showed no significant effects of lunch on task switching, working memory updating and alertness ( P values between 0·07 and 0·79). The present study suggests that school lunch does not seem to have beneficial effects on children’s cognitive functions regarding the conducted tests at early afternoon. Together with our previous studies, we conclude that school lunch in general has no negative effects on cognitive performance in children. However, beneficial effects seem to be restricted to a relatively short time period after eating lunch.

Changes in water and sugar-containing beverage consumption and body weight outcomes in children - Muckelbauer, Rebecca; Gortmaker, Steven L.; Libuda, Lars; Kersting, Mathilde; Clausen, Kerstin; Adelberger, Bettina; Müller-Nordhorn, Jacqueline (British Journal of Nutrition)
Abstract An intervention study showed that promoting water consumption in schoolchildren prevented overweight, but a mechanism linking water consumption to overweight was not substantiated. We investigated whether increased water consumption replaced sugar-containing beverages and whether changes in water or sugar-containing beverages influenced body weight outcomes. In a secondary analysis of the intervention study in Germany, we analysed combined longitudinal data from the intervention and control groups. Body weight and height were measured and beverage consumption was self-reported by a 24-h recall questionnaire at the beginning and end of the school year 2006/2007. The effect of a change in water consumption on change in sugar-containing beverage (soft drinks and juices) consumption, change in BMI (kg/m 2 ) and prevalence of overweight and obesity at follow-up was analysed using regression analyses. Of 3220 enroled children, 1987 children (mean age 8·3 ( sd 0·7) years) from thirty-two schools were analysed. Increased water consumption by 1 glass/d was associated with a reduced consumption of sugar-containing beverages by 0·12 glasses/d (95 % CI −0·16, −0·08) but was not associated with changes in BMI ( P =0·63). Increased consumption of sugar-containing beverages by 1 glass/d was associated with an increased BMI by 0·02 (95 % CI 0·00, 0·03) kg/m 2 and increased prevalence of obesity (OR 1·22; 95 % CI 1·04, 1·44) but not with overweight ( P =0·83). In conclusion, an increase in water consumption can replace sugar-containing beverages. As sugar-containing beverages were associated with weight gain, this replacement might explain the prevention of obesity through the promotion of water consumption.